COMPETIÇÃO INTRA E INTERESPECÍFICA EM UMA POPULAÇÃO DE TREVOS (OXALIS SPP. - OXALIDACEAE), I.R.D.E.R., AUGUSTO PESTANA, RS - BATISTA, FABIANE; SANTOS, FABIO L. D.; MEGIER, GABRIELA; ADAMSKI, JANETE M.; LIBARDONI, JULIANA; VOLTOLINI, JULIO C.; SILVA, LIGIA; JACOBOSKI, LUCILENE I.; CIDADE, MARCIA; GEROLDINI, MÁRCIO; et al. (Salão do Conhecimento, 2013)
Resumo